Biossíntese de lipídios por Rhodotorula mucilaginosa CCT 7688 a partir de hidrolisado de cascas de soja - Rocha, Keslei Rosendo da (2019)
Lipids are organic molecules that are part of the constitution of living things and their food, being generally obtained through oil plants such as soybeans, for example, but also through the use of microorganisms such as yeasts. These have been studied extensively because of their rapid growth rate, possibility of expansion of the production scale and not being subject to typical crop pests. As a way of minimizing the costs of producing yeast lipids industrial coproducts can be used in the process by offering an alternative source of carbon and also minerals essential for growth. Thus, this work had as objective the production of lipids through the use of the yeast Rhodotorula mucilaginosa CCT 7688 in culture medium composed of hydrolysate obtained from soybean hulls. The soybean hulls used in this study were composed mainly of cellulose (39.11 %), hemicellulose (27.22 %) and lignin (14.73 %). Among the analyzed metals, the highest concentrations were aluminum (502.01 mgkg-1), zinc (42.20 mgkg-1) and manganese (40.12 mgkg-1). In order to determine the best hydrolysis conditions for the hulls aiming at a higher release of fermentable carbohydrates, tests were carried out evaluating the influence of hulls granulometry (without grinding or grinded with a mean particle size 1 mm), pressure and temperature inside the autoclave (0.5 atm e 111 °C, 1.1 atm e 122 °C, 1.5 atm e 127 °C) and de H2SO4 concentration (1,2 mmolg-1, 1,5 mmolg-1 and 1,8 mmolg-1). The solid-liquid ratio (1:8.8) and total reaction time (60 min) were fixed. The best determined conditions were: 1.1 atm, 122 °C, H2SO4 1.8 mmolg-1 and hulls with particle size 1 mm. Under these conditions 18.10 gL-1 of total reducing sugars were produced. In the first tests using the hydrolysate obtained from the best studied conditions, 9.11 ± 0.01 gL-1 of biomass were produced with 5.30 ± 0.68 % of lipids content, reaching 0.48 ± 0.06 gL-1 of total lipids after 240 h of cultivation. Cultures were carried out in a medium that simulated the carbohydrate concentrations present in the hydrolysate of soybean hulls (sugars mix), where 6.93 ± 0.02 gL-1 of biomass were produced with 11.49 ± 0.17 % of lipids content, reaching 0.79 ± 0.01 gL-1 of total lipids after 240 h of cultivation. In order to maximize the production of total lipids experimental designs (CCD 2³) were proposed, where the C/N ratio, MgSO4 7 H2O concentration and initial pH were the factors studied using as carbon sources xylose, arabinose, glucose and the concentrated hydrolysate. For the latter, C/N 80, MgSO4 7 H2O 1.5 gL-1 and initial pH 3.5 were the conditions that guaranteed best results: 7.26 gL-1 of biomass with 19.41 % of lipid content and 1.41 gL-1 of total lipids after 240 h of cultivation, which represented an increase of 66 % in relation to the first tests with the hydrolysate and 44 % in relation to the mix that simulated the concentration of the carbohydrates in the hydrolysate. Different cultivation strategies were also evaluated in order to increase lipid production. The "hydrolysate (20 gL-1) and addition of glucose (10 gL-1) after 72 h" fed-batch strategy was the one with better results: 11.92 ± 0.02 gL-1 of biomass composed by 29.28 ± 0.13 % of lipids, reaching 3.49 ± 0.01 gL-1 of total lipids after 144 h of cultivation. The lipids produced in this strategy were characterized by ¹H NMR and GC/MS, where the composition of oleic acid (66.92 %) and palmitic acid (24.62 %) was determined, among others, in smaller fractions. These results showed the potential when soybean hulls hydrolysate was used as a source of carbon and nutrients for lipid biosynthesis by R. mucilaginosa CCT 7688.